Prevention of common oral diseases among Senior Secondary School Students in Enugu State, Nigeria - Okoli, Scholastica Chidi; Ogbalu, I. A. (Orapuh Journal, 2021)
Introduction Oral diseases are major threats to general health but can be prevented by the adoption of healthy oral hygiene practices. Purpose This study was aimed at ascertaining the prevention of common oral diseases among selected Senior Secondary School students in Enugu State, Nigeria. Materials and Methods The descriptive survey design was adopted for the study. The population comprised of all the 50,736 Senior Secondary School students in government-owned secondary schools in Enugu State, Nigeria. A sample size of 900 participants was used for the study. This sample was generated through a multistage simple random sampling procedure. One research question and three hypotheses were posed for the study. A researcher-made questionnaire, Prevention of Common oral diseases (PCOD), was the instrument used for the study. The reliability of the instrument was tested using Kuder Richardson’s formula – 20 (K –R20) at a 0.05 level of significance and a reliability coefficient of 0.97 was derived. Data was collected from the responses of the respondents to the questionnaire. Frequencies, percentages, and chi-square statistics at a 0.05 level of significance were utilized for the descriptive and inferential analyses of the data. Results Results showed that the adherence of the respondents to certain preventive measures was high. 98.9% of the students cleaned their teeth in the morning. However, students didn’t adhere to the practice of dental visits and reducing the consumption of refined carbohydrates satisfactorily. There was a significant difference in the preventive measures adopted by students in urban and rural areas (p<0.05). But, there was no significant age- and gender-difference in the preventive measures adopted by the students (p>0.05). Conclusion Effective sensitization campaigns on the preventive measures for oral diseases need to be carried in all schools to ensure adherence to good oral hygiene practices.